Impaired bone healing in multitrauma patients is associated with altered leukocyte kinetics after major trauma - Bastian OW (Dove Medical Press, 2016)
Okan W Bastian,1 Anne Kuijer,1 Leo Koenderman,2 Rebecca K Stellato,3 Wouter W van Solinge,4 Luke PH Leenen,1 Taco J Blokhuis1 1Department of Traumatology, 2Department of Respiratory Medicine, 3Department of Biostatistics and Research Support, Julius Center, 4Department of Clinical Chemistry and Hematology, University Medical Center Utrecht, Utrecht, the Netherlands Abstract: Animal studies have shown that the systemic inflammatory response to major injury impairs bone regeneration. It remains unclear whether the systemic immune response contributes to impairment of fracture healing in multitrauma patients. It is well known that systemic inflammatory changes after major trauma affect leukocyte kinetics. We therefore retrospectively compared the cellular composition of peripheral blood during the first 2 weeks after injury between multitrauma patients with normal (n=48) and impaired (n=32) fracture healing of the tibia. The peripheral blood-count curves of leukocytes, neutrophils, monocytes, and thrombocytes differed significantly between patients with normal and impaired fracture healing during the first 2 weeks after trauma (P-values were 0.0122, 0.0083, 0.0204, and <0.0001, respectively). Mean myeloid cell counts were above reference values during the second week after injury. Our data indicate that leukocyte kinetics differ significantly between patients with normal and impaired fracture healing during the first 2 weeks after major injury. This finding suggests that the systemic immune response to major trauma can disturb tissue regeneration. Keywords: SIRS, inflammation, neutrophils, myelopoiesis, regeneration